Pre-analytical variations affecting INR measurement for dose tailoring of anticoagulants. - Shamma, Samir Nabhan (AUC Knowledge Fountain, 2019)
Although warfarin (WRN) has been used as oral anticoagulant therapy for over 60 years, it remains a challenge to use in clinical practice since several factors may complicate WRN response which expressed is in international normalized ratio (INR). Numerous patient related variations may affect the adequacy of the assay interpretation which may lead to into poor clinical management. This study aims investigating the impact of age, sex, hemoglobin, packed cell volume (PCV), and albumin levels as well as patient adherence and drug-drug interactions (DDI) on coagulation monitoring results. INR was recorded in patients under WRN maintenance therapy (n=96). Hemoglobin, PCV and albumin levels were recorded. Patient adherence to WRN regimen was analytically assessed using an LC-MS/MS method. In the study group, 45% achieved the target INR (2 – 3.5). Anemia was more prevalent among uncontrolled patients where 38% suffered severe anemia (5 male and 15 female). Abnormal PCV was observed in 47% of uncontrolled patients (7 male and 18 female). There was a significant difference in age, hemoglobin, and PCV and albumin level between patients who achieved optimum INR and those who did not. Moreover, good relationship was obtained between WRN concentration and INR (R2=0.622) by excluding samples showing DDI (n=16), abnormal albumin (n=9) or steroid (n=6) abnormalities. Analytical assessment revealed lack of adherence to WRN dose. In addition, unsupervised drug consumption or missing prescribed doses was observed in at least 5% of the cases. In conclusion, based on the poor correlation of INR with plasma WRN in these cases, albumin level, hemoglobin, and PCV abnormalities along with DDI are all important factors to consider during clinical monitoring of WRN response. It also highlights the significance of monitoring plasma WRN to assess adherence to scheduled doses. These findings may help to identify the patients who will require closer monitoring for optimizing the outcomes of WRN therapy.